2007
DOI: 10.1002/j.0022-0337.2007.71.6.tb04340.x
|View full text |Cite
|
Sign up to set email alerts
|

Occupational Exposure to Bloodborne Pathogens and Management of Exposure Incidents in Nigerian Dental Schools

Abstract: The goal of this study was to determine the frequency of occupational exposures to bloodborne pathogens amongst Nigerian clinical dental students, their HBV vaccination status, and reporting practices. A cross-sectional study of all clinical dental students in the four Nigerian dental schools was carried out by means of an anonymous self-administered questionnaire that asked questions on demography, number and type of exposure, management of the exposures, personal protection against cross infection, and the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
44
2
2

Year Published

2008
2008
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(54 citation statements)
references
References 18 publications
4
44
2
2
Order By: Relevance
“…Proper hepatitis B vaccination is the best procedure to prevent contagious transmission during dental treatments [ 7 ]. The prevalence of hepatitis B vaccination among dental health workers varies from 38% to 100% [ 3 ], [ 7 ], [ 13 ], [ 14 ], [ 15 ], [ 16 ], [ 17 ]. In the present study, the majority (90%) reported having been vaccinated against hepatitis B.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Proper hepatitis B vaccination is the best procedure to prevent contagious transmission during dental treatments [ 7 ]. The prevalence of hepatitis B vaccination among dental health workers varies from 38% to 100% [ 3 ], [ 7 ], [ 13 ], [ 14 ], [ 15 ], [ 16 ], [ 17 ]. In the present study, the majority (90%) reported having been vaccinated against hepatitis B.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, despite the considerable emphasis placed on the importance of adherence to these protocols, studies have shown that few dentists actually adhere to the standardized infection control procedures in their daily practice [ 4 ], [ 8 ], [ 9 ], [ 10 ], [ 11 ]. Moreover, several studies worldwide have investigated undergraduate dental students’ knowledge and attitudes regarding infection control, finding very poor compliance with infection control guidelines and indicating the need to improve the knowledge and attitudes regarding infection control [ 3 ], [ 7 ], [ 12 ], [ 13 ], [ 14 ], [ 15 ]. To date, no published data exists regarding infection control practices among dental students in Saudi Arabia.…”
Section: Introductionmentioning
confidence: 99%
“…23 Our study results regarding this issue are much better than the results quoted in two other studies in Germany and Nigeria where health care workers' vaccination percentage was found to be only 37.9 and 18.1% respectively. 24,25 Stakeholders who are seeing vaccination as a only tool to prevent spread of these infections among health care workers are really alarmed by this lack of adherence to the vaccination schedule and nonadoption of universal precautions by health care workers in their routine practices. This fact can be verified from this study in which almost one fourth of the participants still don't wear gloves (17.1%), or dispose off Sharps adequately (19.4%) in the course of their work.…”
Section: Discussionmentioning
confidence: 99%
“…Varying figures were reported from different countries of the world regarding complete vaccination (≥3doses) against hepatitis B virus among HCWs, ranging from 68% in Turkey (Azap et al, 2005), 61.5% in India (Setia et al, 2013), 56.1% in Syria (Yacoub et al, 2010), 41.2% in Germany (Schenkel et al, 2008) to 37.9% in Nigeria (Sofola et al, 2007).…”
Section: Hepatitis B Vaccination Among Hcwsmentioning
confidence: 99%